(untitled) (Revista Electrónica REDINE, 2018)
The aim of the research was analyze the assessment by the director of the National Education Unit "Gran Mariscal de Ayacucho, about the preparation, design and implementation of Pedagogical Classroom Projects. The research design was field, descriptive, for execution, a sample of twenty (20) teachers, who answered a questionnaire type instrument. The technique of data analysis was the statistical frequency percentage. Among the conclusions found are cited: a) The director in its role as guarantor of the educational process, evaluates whether teachers take into account when planning Pedagogical Classroom Projects, the constructivist approach demanded by the current curriculum design. However, fostering a comprehensive learning environment as one of the objectives of the PPA, in relation to the student. b) A significant number of teachers believe that the director in planning assesses whether pedagogic projects of school, teachers do to educate for democracy and social harmony. c) 72% of teachers acknowledged that the principal evaluates rarely, if these crosscutting integrated into the fields of being, doing and sharing through concepts and procedures.